Use of Plant Resources by Merosargus (Diptera, Stratiomyidae, Sarginae) Larvae - Julio C. R. Fontenelle; Flávia E. C. Viana-Silva; Rogério P. Martins (Psyche: A Journal of Entomology)
The genus Merosargus (Loew) has 142 described species. This great diversity in the genus could be explained by larvae resource-use specialization. However, information on larval habitats is still very scarce. In Merosargus species, adult males defend oviposition sites, and this territorial behavior may lead to interspecific competition and make even more important the specialization and niche partitioning to prevent competitive exclusion. This study identified substrate types used as a resource by Merosargus larvae and investigated the degree of specialization and overlap in resource use by different species at an Atlantic forest remnant in Minas Gerais, Brazil. Every potential resource, especially those with adults in the vicinity, was collected opportunistically from October 2001 to October 2004. In total, 292 individuals from 12 Merosargus species collected from 21 resource types and 15 plant species were reared in the laboratory. Plant species included herbs, vines, palms, and trees. Six Merosargus species were reared from only one resource type, and each resource type was used, on average, by less than two Merosargus species. Thus, Merosargus species exhibited a high degree of specialization and small overlap in larval resource selection, which could explain the high local and global diversity of the genus.